Correlation between cultivation methods and quality in some vegetable species - Takácsné Hájos, Mária (Acta Agraria Debreceniensis, 2012)
Quality parameters of 5 table root varieties were tested on 3 sowing dates with different cultivation methods: open field on 15 April and 9 July 2010 and under plastic tents on 19 August. The highest red pigment content (betanin) was measured in the varieties Akela and Mona Lisa (~ 80 mg 100 g-1) of the second (July) crop. This crop is in general use in Hungary. In comparison, in the late sown varieties (August, under plastics) a further pigment increase (10–20 mg 100 g-1) was observed in the same varieties as related to the earlier sowing dates. Yellow pigments (vulgaxanthins) showed similar trends. Roots of the late sowing date (with harvest in December) contained the highest vulgaxanthin values (103.3–124.18 mg kg-1).Varieties reacted differently to temperature changes during the production period and thus to sugar accumulation. In the second crop (July) higher water soluble solids content was measured on the average of varieties (10.12%) in comparison to the April sowing (7.76%). Beetroots of the spring sowing are recommended for fresh market while the second (July) crop with autumn harvest can satisfy industry requirements. Late sowing under unheated plastic tents supply us with fresh beetroot in late autumn and early winter and prolong the usability of plastic tents. Six lettuce species/subspecies were tested in the open field and under plastic tents in 3 repetitions for nitrate nitrogen, vitamin-C, polyphenol (gallus acid equivalent – mg GAE 100 g-1) and mineral element (Ca, K, Mg, Na) contents. Our measurements showed lower nitrate nitrogen values under plastic than in the open field (89.10± 8.13 and 127.06±14.29 mg kg-1) on the average of genotypes. Lettuce grown in the field had higher vitamin-C content (1.4 mg%) which is nearly 50% more than in plants under plastic. The highest polyphenol content was found in samples from the field with a conspicuous value of 804.17±56.47 mg GAE 100 g-1 in Piros cikória. Samples grown under plastic were richer in mineral elements (Ca, K, Mg, Na) which can be explained by the higher nutrient content of the soil. In this environment superior Mg content was observed in Edivia (4616.33±311.21 mg kg-1). Besides the well- known headed lettuce, Piros cikória (Red chicory),the red leaved Lollo Rossa and Tölgylevel (Oak leaf lettuce) should bementioned which well deserve further testing in order to supply us with nourishing, healthy food.